Effects of the linewidth enhancement factor on filamentation in 1.55 mu m broad-area laser diodes - Heo, DC; Han, IK; Lee, JI; Jeong, JC; Cho, SH (IOP PUBLISHING LTD, 2003)
Broad-area laser diodes with different linewidth enhancement factors (a-factors) of 2 and 4 have been fabricated on 1.55 mum multi-quantum well structures. Far-field measurements show that the filamentation of the laser diodes is closely related to the alpha-factor. The full width at half maximum (FWHM) of the far-fields and the filamentation were reduced in the laser diodes with smaller alpha-factors. As the injection current increased, the FWHM of the far-fields also increased regardless of the value of the alpha-factor. This phenomenon is explained by the reduction of the filament spacing as the injection current increased. A qualitative explanation of filamentation mechanisms is given by introducing the notion of sub-aperture.
Keywords: QUANTUM-WELL LASERS; SEMICONDUCTOR-LASERS